Adolescent stress accelerates postpartum novelty recognition impairment in 5xFAD mice - Leitzel, Owen; Francis-Oliveira, Jose; Khedr, Shaimaa M.; Ariste, Lila; Robel, Stefanie; Kano, Shin-ichi; Arrant, Andrew; Niwa, Minae (Frontiers in Neuroscience, 2024)
Pregnancy and the postpartum period induce physiological changes that can influence women's cognitive functions. Alzheimer's disease (AD) has a higher prevalence in women and is exacerbated by early life stress. In the present study, we found that late adolescent social isolation combined with the experience of pregnancy and delivery accelerates the onset of cognitive deficits in 5xFAD dams, particularly affecting their ability to recognize novelty. These cognitive deficits manifested as early as 16 weeks, earlier than the usual timeline for these mice, and were closely associated with increased levels of corticosterone, suggesting dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis. Notably, the presence of β-amyloid plaques in brain regions associated with novelty recognition did not significantly contribute to these deficits. This highlights the potential role of stress and HPA axis dysregulation in the development of cognitive impairments related to AD, and underscores the need for further investigation.